2003
DOI: 10.1002/joc.960
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of spatial and seasonal variability: Austrian precipitation during the 20th century

Abstract: The purpose of this investigation is to demonstrate the usability of objective methods to study the variability of precipitation and hence to contribute to a better understanding of spatial and seasonal variability of Austria's precipitation climate during the 20th century.This will be achieved by regionalizing the intra-annual variability of seasonal precipitation distributions during three non-overlapping 33 year samples (1901-33, 1934-66, 1967-99). Monthly precipitation totals were extracted at 31 Austrian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 13 publications
3
21
0
1
Order By: Relevance
“…No general precipitation trends can be found for the whole of Austria. However, due to the important influence of the Alpine ridge, Austria has to be divided into 3 different precipitation regions (Matulla et al 2003). The most drought-prone region occurs in the northeastern part of Austria and is highly correlated with patterns in the neighboring Czech territory, as confirmed in this study.…”
Section: Regional and Large-scale Contextsupporting
confidence: 79%
“…No general precipitation trends can be found for the whole of Austria. However, due to the important influence of the Alpine ridge, Austria has to be divided into 3 different precipitation regions (Matulla et al 2003). The most drought-prone region occurs in the northeastern part of Austria and is highly correlated with patterns in the neighboring Czech territory, as confirmed in this study.…”
Section: Regional and Large-scale Contextsupporting
confidence: 79%
“…Decreasing precipitation amounts towards the flatter eastern parts result from the predominating continental air masses there. Additionally, the inner alpine valleys feature reduced precipitation amounts due to the rain shadowing of the mountain ranges (compare Figure 2(a); Cebon et al, 1998;Matulla et al, 2003). The observed climatology given in Figure 2(a) covers the period 1981-1990 according to the focus period of this study, but the spatial patterns as well as the magnitudes are comparable to the climatic conditions between 1971 and 1990 shown in Frei and Schär (1998).…”
Section: Data and Study Regionsupporting
confidence: 57%
“…A similar study was reported in Matulla et al (2003) whereby regionality of Austrian precipitation was identified using EOF and other pattern analysis techniques. The mountainous topography was identified as profoundly affecting the seasonal influence of the prevailing air masses upon precipitation.…”
Section: Introductionsupporting
confidence: 57%